Unpacking the Impact of Asset Structure and Sales Growth on Capital Structure: The Moderating Influence of Profitability - Jamian Purba; Dian Sulistyorini Wulandari; Sri Lestari (Journal of Scientific Interdisciplinary, 2024)
This study explores the impact of asset structure and sales growth on capital structure, emphasizing the moderating influence of profitability. As firms navigate the complexities of financing decisions, understanding how these variables interact is crucial for optimizing capital structure. The findings reveal that asset structure and sales growth significantly affect capital structure, with profitability playing a critical role in moderating these relationships. Firms with substantial tangible assets are better positioned to leverage debt financing, while those demonstrating strong sales growth are viewed favorably by investors and creditors. However, the extent to which sales growth influences capital structure is contingent upon profitability; high profitability enables firms to capitalize on growth opportunities, whereas low profitability may inhibit their capacity to leverage growth potential. Empirical research supports these conclusions, indicating that asset structure, sales growth, and profitability significantly shape capital structure decisions across various industries. Ultimately, this study provides valuable insights for financial managers, highlighting the importance of balancing growth aspirations with profitability to achieve effective capital structure management. This, in turn, can lead to sustained competitive advantage, a state where a firm outperforms its competitors over a prolonged period in a dynamic economic environment.